2010
DOI: 10.1111/j.1469-8749.2009.03564.x
|View full text |Cite
|
Sign up to set email alerts
|

Enabling self‐directed computer use for individuals with cerebral palsy: a systematic review of assistive devices and technologies

Abstract: AIM The purpose of this study was to systematically review published evidence on the development, use, and effectiveness of devices and technologies that enable or enhance self-directed computer access by individuals with cerebral palsy (CP).METHODS Nine electronic databases were searched using keywords 'computer', 'software', 'spastic', 'athetoid', and 'cerebral palsy'; the reference lists of articles thus identified were also searched. Thirty articles were selected for review, with 23 reports of development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 50 publications
1
25
1
2
Order By: Relevance
“…In fact, it (a) constitutes a careful demonstration of the possibility of combining leisure and communication opportunities for post-coma persons with multiple disabilities through assistive technology, (b) adds to the preliminary (encouraging but limited) data available in this context, and (c) strengthens the view that it might be possible to help these persons improve their rehabilitation and life perspectives in a reasonable and affordable way (Bauer et al, 2011;Borg et al, 2011;Davies, Mudge, Ameratunga, & Stott, 2010;De Joode et al, 2012;Häggström & Lund, 2008;Lancioni, Singh, O'Reilly, Sigafoos, Ferlisi et al, 2012).…”
Section: Discussionmentioning
confidence: 90%
“…In fact, it (a) constitutes a careful demonstration of the possibility of combining leisure and communication opportunities for post-coma persons with multiple disabilities through assistive technology, (b) adds to the preliminary (encouraging but limited) data available in this context, and (c) strengthens the view that it might be possible to help these persons improve their rehabilitation and life perspectives in a reasonable and affordable way (Bauer et al, 2011;Borg et al, 2011;Davies, Mudge, Ameratunga, & Stott, 2010;De Joode et al, 2012;Häggström & Lund, 2008;Lancioni, Singh, O'Reilly, Sigafoos, Ferlisi et al, 2012).…”
Section: Discussionmentioning
confidence: 90%
“…Our goal is to identify the shortcomnigs of the current person-computer interfaces and propose a novel solution to reduce them. Davies et al (2010), published a systematic review on the development, use and effectiveness of devices and technologies that enable or enhance self-directed computer access by individuals with CP. The study showed that twenty-four studies had fewer than 10 participants with CP, with a wide age range of 5 to 77 years.…”
Section: Evaluation Of the Driving Interfacesmentioning
confidence: 99%
“…ej., gestos de las manos, de la cara, o de los ojos), sensores inerciales, interfaces cerebrocomputador, comandos de voz o soplidos, señales eléctricas de los músculos, y dispositivos basados en interruptores [10], [11]. La mayoría de tecnologías de asistencia para la interacción -en donde también se incluyen a los dispositivos apuntadores basados en las soluciones mencionadas-no solventan el problema relacionado con la inserción de las TIC en la comunidad con discapacidad [12].…”
Section: Introductionunclassified